The Strategies Used by EFL Students to Learn New Vocabulary - Ika Imaroh; Siti Aisyah; Yudy Prasetyo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2026)
For EFL students, vocabulary mastery is very important, but traditional memorization methods often result in passive knowledge. The vocabulary mastery mechanisms used by seventh-semester EFL students at Universitas PGRI Delta Sidoarjo after attending formal vocabulary classes were analyzed in this study. Ten students were selected through purposive sampling and interviewed in November 2025 using a qualitative descriptive design and semi-structured interviews. Thematic analysis revealed three interconnected themes: (1) Authentic Multimodal Media with Emotional Connections (films, music, social media), (2) Active Practice through Production and Error-Based Learning (conversations, writing, self-practice), and (3) Immediate Meaning Search with Contextual Understanding (online dictionaries with contextual exploration). The results of the study show that advanced EFL students use authentic materials and emotional engagement for deeper encoding and retention, shifting from teacher-dependent learning to independent learning. Compared to mechanical memorization, these techniques are considered simpler, more enjoyable, and more applicable. This study provides insights for creating more successful, steaudent-centered vocabulary training by highlighting the importance of contextual understanding, productive practice, and the transformation of error experiences in vocabulary acquisition.